Seasonal variation in the incidence of parturient disorders of Sahiwal cattle - MANDAL, D K; TYAGI, S; MUKHERJEE, S (The Indian Journal of Animal Reproduction, 2005)
A total of 443 calving records of Sahiwal cows maintained at Military Farm, Meerut, during the period of April, 1994 to March 1999 were analyzed to study the incidence of parturient disorders. The over all incidence of abortion, still birth, premature birth, retention of placenta, dystocia and total parturient disorders were 3.16, 2.70, 0.45, 7.00, 0.90 and 14.21 per cent, respectively. The highest incidence of total parturient disorder was observed during winter (7.00%), followed by summer (3 .84%) and rainy (3 .39%) seasons. The seasons or periods were not found to significantly (P<0.05) affect the incidence of various types of parturient disorders in Sahiwal cattle.